Empowering Santri: The Driving Force Behind Successful Marketing in Pesantren - Aris Dwi Nugroho; Siti Munawwaroh (Nidhomul Haq)
This study aims to examine the role of students in marketing education at the Irsyadul 'Ibad Islamic Boarding School, Jambi. With the number of new students increasing from 118 in 2021/2022 to 216 in 2023/2024, this study explores how students contribute to attracting public interest in registering their children. Qualitative methods were used to understand the meaning and context of the role of students through interviews, observations, and document analysis. The results of the study show that students are active in various religious, social, sports, and arts activities, which serve as effective promotions for the Islamic boarding school. Their involvement in activities such as Yasinan, teaching at the madrasah, and village events improves the image of the Islamic boarding school and attracts public attention. However, there are also negative impacts, such as the risk of a bad image of the Islamic boarding school if marketing is not managed properly. The Irsyadul 'Ibad Islamic Boarding School has implemented a marketing strategy that involves students, including the formation of a creative team and the use of social media. Evaluations are carried out every semester to adjust the strategy to existing developments. This study emphasizes the importance of managing the role of students wisely to maximize marketing potential while minimizing possible risks.